2016
DOI: 10.1007/s00542-016-3032-y
|View full text |Cite
|
Sign up to set email alerts
|

Low-power half-select free single-ended 10 transistor SRAM cell

Abstract: the proposed design consumes 1.38× lesser read power as compared to UDVS10T and 1.67× and 5.02× lesser write power as compared to DF9T and UDVS10T respectively. The proposed design shows 1.8 % improvement in read current variability when compared to DF9T. Lastly, the proposed cell shows 2.21× and 5.25× higher I READ /I LEAK as compared to DF9T and UDVS10T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…15 Finally, Figure 7 (f) shows that the proposed bit-cell has improved by 10.24% (1.11 times) in the mean value of the Read-SNM compared to the counterpart bit-cell in Sinha and Islam. 6 The read failure cases are also observed for the si-MOSFET technology-based bit-cell in Shakouri et al 8 In addition, it is observed that the minimum value of Read-SNM by the suggested bit-cell is about 128 mV, which is higher than the minimum requirement of Read-SNM (i.e., 25% of V dd ). Therefore, the result indicates that the proposed cell has a reasonably good read stability.…”
Section: Read-stability and Write-ability Analyses For Existing Sram ...mentioning
confidence: 77%
See 4 more Smart Citations
“…15 Finally, Figure 7 (f) shows that the proposed bit-cell has improved by 10.24% (1.11 times) in the mean value of the Read-SNM compared to the counterpart bit-cell in Sinha and Islam. 6 The read failure cases are also observed for the si-MOSFET technology-based bit-cell in Shakouri et al 8 In addition, it is observed that the minimum value of Read-SNM by the suggested bit-cell is about 128 mV, which is higher than the minimum requirement of Read-SNM (i.e., 25% of V dd ). Therefore, the result indicates that the proposed cell has a reasonably good read stability.…”
Section: Read-stability and Write-ability Analyses For Existing Sram ...mentioning
confidence: 77%
“…The results presented in Figure 7A show that the proposed bit‐cell with a higher Write‐SNM value has easier data writing than the cells considered for comparison in this study. After the proposed SRAM structure, the bit‐cell in Sinha and Islam 6 . Using the virtual ground design in similar design technology has a robust data transfer feature without the problem of writing conflict.…”
Section: Simulation Results Comparative Analysis and Supplementary Di...mentioning
confidence: 99%
See 3 more Smart Citations